Legal Consequence of Land Rights Related To Complete Systematic Land Registration Program (PTSL) In Mojokerto City - Tomi Halim Adianjaya (Faculty of Law, Merdeka University Surabaya, 2019)
Land registration and issuance of certificates aim to provide legal certainty over property rights to land and to create orderly land administration. One of the Government's programs in achieving this goal is implementing a Complete Systematic Land Registration through the enactment of the State Minister for Agrarian and Spatial Planning/Head of the National Land Agency Number 1 of 2017 on Acceleration of the Implementation of Complete Systematic Land Registration. Problems to be discusse this study iclude: (1) Is the object of land to be registered in this program Petok D or Letter C? (2) Can the certificate of Ownership Rights guarantee legal certainty for the rights holders? The problem approach used is the normative legal approach. The data consists of secondary and primary data. Data analysis is carried out by using qualitative analysis. The results of this study indicate that: (1) Implementation of Complete Systematic Land Registration on land that has not been certified based on provisions of the Regulation of the State Minister for Agrarian and Spatial Planning or Head of National Land Agency Number 1 of 2017 includes: determination of PTSL activity location, establishment and determination of PTSL Adjudication Committee, counseling, juridical and physical data collection of the land, land checks, announcements of physical data and juridical data on land and proof of rights, issuance of decisions on the awarding or recognition of land rights, bookkeeping and issuance of certificates of land rights and submission of certificates of land rights. (2) the legal consequences of certification of the results of complete systematic land registration are the objections of other parties to the land registration process through PTSL carried out by the registrant, the applicant is difficult to complete the land registration application requirements through PTSL, and the community's understanding is still low against the law in the land sector. Suggestions to be provided in this study are: (1) Mojokerto City Government together with the City Land Office should further improve services to the community, especially in the land sector. (2) Mojokerto City Land Agency should increase legal counseling or socialization about land.